Popularization of health in Polish philately: Part 1 — postage stamps - Smoła, Marek (Health Promotion & Physical Activity, 2022)
The article constitutes an attempt of presenting the phenomenon of popularization of health, health protection, achievements in medicine and people connected to medicine through a postal stamp. A stamp is an object of collection and the subject of the more and more elitist hobby but at the same time it is an element of correspondence used by many people, including a sender and a recipient in numerous countires. That is why, reaching for such a topic in different emissions of postal stamps can spread the knowledge about different almost all aspects of human civilization. This publication is a compilation of information about postal stamps issued by Polish Post Office between 1919 and 2022 and referring in multiple ways and methods to the widely understood topic of health and its protection. The aim of the work was to present the stamps in chronological order, including the emission title, circumstances and occasions of the emission, circulation numbers and short presentation of events, phenomena, people and objects depicted on the stamps.